Infection Rate After Using Metal Plate And Screws Versus Intramedullary Nails In Orthopedic Opearations On Bones Diaphase Of (Humerus-Femur-Tibia) - جوني أحمد; يوسف صفوان; زهيرة سام (Latakia University Journal -Medical Sciences Series, 2022)
Background : Infection after osteosynthesis is one of the biggest challenges facing orthopedic surgeons, as it may cause disruption or loss of function of the affected limb, or amputation and death at other times. The research aims to reduce the incidence of infection after osteosynthesis by choosing the appropriate method of fixation and the least risk of infection . Patients and Methods : An analytical study was conducted to review data of patients admitted to the Orthopedic Surgery Department at Tishreen University Hospital in Lattakia, who underwent fixation of bone fractures (humerus, femur, tibia) with metal plates and screws or with intramedullary nails during 2019-2020, counting 316 patients . Those who achieve the search inclusion criteria . Results : Infection developed in 29 patients (9.2%), infection with platelets (12.7%) and nails (6.7%), early infection (58.6%), the most isolated bacteria were Staphylococcus aureus (37.9%). The risk of infection was higher in cases of age over 60 years (P=0.02), diabetes mellitus (P=0.02), duration of hospital stay before surgery of more than 5 days (P=0.01), and duration of surgery more than 2 hours (P=0.01). ) and the need to transfuse more than two units of blood (P = 0.02) Conclusion : Plates infection rate (12.7%) was higher than that of Nails (6.7%). The following factors: age over sixty years, diabetes mellitus, hospital stay before surgery for more than five days, duration of surgery for more than two hours, and the need to transfuse more than two blood units , carry a greater risk of developing infection around the implants.